Xanthomonas wilt of banana (BXW) in Central Africa: opportunities, challenges, and pathways for citizen science and ICT-based control and prevention strategies - McCampbell, M.; Schut, Marc; Bergh, Inge van den; Schagen, Boudy van; Vanlauwe, Bernard; Blomme, Guy; Gaidashova, S.V.; Njukwe, E.; Leeuwis, Cees (Informa UK Limited, 2018)
Xanthomonas Wilt of Banana (BXW) is a complex problem in the African Great Lakes Region that is affecting the livelihoods of millions of smallholder farmers. Since the first disease reports from Uganda and the Democratic Republic of Congo in 2001, BXW has been studied widely. The majority of these studies focus on the technological or biophysical dimensions, while aspects and influence of socio-cultural, economic and institutional dimensions only recently started to gain attention. This paper provides an in-depth analysis of the broader BXW problem using a systems perspective, with the aim to add to the understanding about reasons for poor uptake of appropriate disease management practices, and limited ability to prevent rather than control BXW in the region. We comprehensively describe and analyse the various problem dimensions, and determine relations with data, information, knowledge, and connectivity. Building on this, the paper explores and discusses entry-points for the use of Information and Communication Technologies (ICT) and citizen science tools to better address BXW in banana production systems.